Risk factors for urinary incontinence in patients undergoing radical robot-assisted prostatectomy - A. M. Shvedov; K. B. Kolontarev; A. V. Bormotin; V. V. Dyakov; A. A. Vitoslavsky; D. Yu. Pushkar (Вестник урологии)
Introduction. Prostate cancer (PCa) is one of the most common cancers among men, and the tactic to treat this disease stage-depends directly. The “gold” standard for localized PCa is radical robot-assisted prostatectomy (RARP). Patients often have excessive surgery requirements and are concerned about the development of postoperative complications. One of the most frequent functional complications after this operation is urinary incontinence (UI), whose formation mechanism is not fully understood. Clinical studies have described many UI predisposing factors, but the results obtained are often contradictory, which requires a repeated and deeper study of the issue.Objective. To identify predisposing factors for urinary incontinence in patients undergoing radical robot-assisted prostatectomy.Materials & methods. The search results for the scientific databases PubMed, Medline, Web of Science, Embase, Cochrane Library and PEDro, Wang-fang Database and CNKI, Edline were analyzed for the queries "robot-assisted prostatectomy", "radical prostatectomy", "incontinence", "predictors", "urinary incontinence".Results. The predisposing factors to UI after RARP were studied. The review discusses and illustrates in detail all known predisposing factors for UI and shows the inconsistency of the data obtained by different researchers, which once again emphasizes the need for further study of this issue.Conclusion. Despite the long history of studying postoperative complications of RARP, reliable and consistent data on all the risks of UI after RARP have not yet been obtained. Therefore, this literature review summarizes and analyzes the results of the latest research in recent years.